2004
DOI: 10.1111/j.1365-2265.2004.02009.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormones in hereditary angioneurotic oedema

Abstract: In view of these results, the monitoring of progesterone and SHBG levels can prove useful in the prediction of attacks in hereditary angioneurotic oedema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 19 publications
2
30
0
6
Order By: Relevance
“…Symptoms often worsen during puberty, particularly in females 3, 14, 31, 32. Onset of symptoms may occur with the introduction of estrogen‐containing medications for acne or birth control 17.…”
Section: Resultsmentioning
confidence: 99%
“…Symptoms often worsen during puberty, particularly in females 3, 14, 31, 32. Onset of symptoms may occur with the introduction of estrogen‐containing medications for acne or birth control 17.…”
Section: Resultsmentioning
confidence: 99%
“…Visy and colleagues 11 showed that, in 44 women with HAE, the frequency of attacks correlated with estrogen and progesterone levels. The female sexual hormones act on several proteins, including the kallikrein-kinin system.…”
Section: Physiopathologymentioning
confidence: 98%
“…Önceden alınmış olan progesteron içeren ekzojen preparatların, endojen progesteronlara karşı duyarlılık doğuruyor olabileceği ileri sürülmüştür. Bu görüşe göre ekzojen progesteronlar antijenik özellikte olduğundan antikor oluşumuna neden olmakta, oluşan antikorlar da endojen progesteronlarla reaksiyona girip premenstrüel dönemde immün yanıta yol açmaktadır (2). Ancak bizim olgularımızın progesteron içeren ilaç kullanım öyküsü yoktu ve bu durum patogenezde başka faktörlerin de rolünün olabileceğini düşündürmektedir.…”
Section: Discussionunclassified
“…Çeşitli kutanöz ve mukokutanöz bulgular siklik bir şekilde menstrüel siklusun luteal fazında başlar, menstrüel kanamanın başlamasıyla birlikte sonlanır (1). Klinik semptomları arasında egzama, vezikül, püstül, eritema multiforme, ürtiker ve anafilaksi vardır (2). Bu yazıda 4-5 yıl sonra tanı alabilmiş, ürtikeryal lezyonlarla seyreden 2 OPD olgusu sunulmaktadır.…”
Section: Introductionunclassified